Does photodynamic therapy with methylene blue affect the mechanical properties and bond strength of glass-fiber posts in different thirds of intraradicular dentin? - Strazzi-Sahyon, Henrico Badaoui [UNESP]; de Oliveira, Murilo Silva [UNESP]; da Silva, Paloma Pereira [UNESP]; Banci, Henrique Augusto [UNESP]; de Melo, Fernanda Santos [UNESP]; Martinez, Carolina Martins Teixeira [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Gomes Filho, João Eduardo [UNESP]; Dezan Junior, Eloi [UNESP]; Santos, Paulo Henrique dos [UNESP]; Araújo, Gustavo Sivieri de [UNESP] (Elsevier, 2020)
Background: There are few studies on the influence of methylene blue as a photosensitiser on the mechanical properties and adhesion of glass-fiber posts to intraradicular dentin. Thus, this in vitro study aimed to evaluate the influence of photodynamic therapy with a methylene blue photosensitizer on the Martens hardness, elastic modulus, and bond strength of glass-fiber posts in different thirds of intraradicular dentin. Methods: Eighty bovine teeth were divided into the following five groups: a control using deionized water, and four other groups according to the methylene blue concentration (50 mg/L or 100 mg/L) and substrate treatment (with or without red laser action). Ultramicrohardness test was used to evaluate the mechanical properties in different regions of the root dentin (n = 8). Push-out analysis was evaluated using a universal testing machine (n = 8). Data were subjected to the Kruskal–Wallis test, followed by Dunn's test for comparing groups, and the Friedman test for comparing thirds (α = 0.05). Representative scanning electron microscopy images were obtained. Results: In general, methylene blue in distinct concentrations, with or without laser action, did not cause differences in the mechanical properties or bond strength in different regions of root dentin (P > 0.05). Methylene blue at a higher concentration, activated with laser, produced lower bond strength values in the middle third of the root canal (P < 0.05). Conclusions: Methylene blue at 50 mg/L had no influence on the mechanical properties of the bovine tooth and the bond strength of the glass-fiber posts to intraradicular dentin.
Keywords: Dentin; Elastic modulus; Hardness; Methylene blue; Photodynamic therapy; Push Out